Administrative and legal regulation of licensing for medical practice (Law and Safety, 2024)
The article is devoted to the peculiarities of legal regulation of licensing for medical practice. The provisions of laws and regulations governing the procedure for obtaining a licence to practice medicine are studied. The scientific works of scholars in the fields of law, medicine, and public administration who have studied legal relations in the field of healthcare and licensing are studied. Recommendations for amending the legislation are formulated.The author proposes a definition of licensing for medical practice as a means of state regulation of medical care and medical assistance compliance with the established licensing conditions with a view to protecting the life and health of patients and ensuring the provision of quality medical services.The article establishes that there are certain peculiarities of licensing for medical practice in comparison with other types of economic activity. A specially created licensing commission of the Ministry of Health of Ukraine reviews documents for obtaining a licence. The licensing regulations set out specific personnel, technological and organisational requirements that the founders of healthcare facilities must meet before submitting documents for a licence. A special package of documents is prepared to be attached to the licence application and provides for the description of the material and technical base and personnel of the healthcare facility. The activities of the entire healthcare facility, rather than individual healthcare professionals, are subject to licensing.A number of proposals for amendments to the legislation are proposed, namely: 1) to consolidate the concept of medical service as a separate, specific type of medical procedure, diagnosis of a particular disease, rehabilitation, cosmetic care, health massage, paid examination; 2) to define in the licensing conditions more detailed technological requirements for the area of certain premises of a healthcare facility and medical equipment necessary for the treatment of certain diseases; 3) the author supports the position that it is expedient to develop and adopt the Medical Code of Ukraine as a comprehensive legislative act which would regulate legal relations in the field of healthcare.
Keywords: medical practice; licensing; legal regulation; licensing conditions; healthcare; medical activity.